GAYA KEPEMIMPINAN, KOMITMEN ORGANISASI DAN AKUNTABILITAS TERHADAP ORGANIZATION CITIZENSHIP BEHAVIOR DI INSTITUSI MILITER (TNI-AD) KOTA BENGKULU - Nila Aprila; Eka Sepriani (Jurnal Akuntansi, 2017)
This research evaluates the effect of leadership style, organizational commitment and accountability towards organizational behavior in Military Institution in Indonesia. Data was collected by survey method in TNI-AD located in Kota Bengkulu. One hundred seventy questionaires gathered and analized with smartPLS. The result of this research shows that leadership style, organizational commitment and accountability influences organization citizeship behavior. This research inspired by the phenomenon that there is little research on military area regarding accountability, either in Indonesia or in the world. Thus, this research will give a siginificant literature contribution based on the empirical data analyzes in Military Institution in Indonesia.Keywords: leadership style, organizational commitment, accountability and organization citizenship behavior.